ANALISIS PERSEPSI DAN MOTIVASI MASYARAKAT PEMANFAAT TERHADAP MANFAAT SUMBERDAYA HUTAN LINDUNG PULAU TARAKAN - Sutrisno, Adi; Kartodihardjo, Hariadi; Darusman, Dudung; Nugroho, Bramasto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
The research aims is to find the main causes of disharmony between behavior ofusers community and the management objectives of Protection Forest Resource of TarakanIsland that reviewed based on the perceptions and motivations. Based on the researchresults: First, the level of perception of the users of Protection Forest Resource of TarakanIsland included in the medium category, but for the functional benefits and the existentialbenefits included in the low category. While, the level perception of the existential benefitsincluded in medium category and other benefits include high category. Second, the level ofeconomic and environmental motivations of users’ communities in utilization of ProtectionForest Resource of Tarakan Island is low, but the level of social motivation toward ProtectionForest Resource of Tarakan Island is high. Third, the level of public perception of functionalbenefits is low. Low levels of economic motivation and the motivation of social environmentincluding the high motivation of the users’ community in utilization Protection ForestResource of Tarakan Island become the main causes of disharmony between behavior ofusers’ community and the management objectives of Protection Forest Resource of Tarakan Island.